Phase‐Only Holographic Assisted Planar Printing for Massively Multiplexed Optical Display and Encryption. Issue 22 (1st September 2022) - Wei, Yunxuan; Hu, Tie; Feng, Xing; Zhao, Ming; Yang, Zhenyu
Abstract: Multiplexed planar printings, made of single or few layer micro and nano optical platforms, are essential for high capacity display, information storage, and encryption. Although they are developed rapidly, the demonstrated channels are still limited and also lack instantaneity. Here, holograms and printings, always regarded as two independent information coding domains with totally different principles, are combined together through this proposed angle multiplexing framework, leading to multiplexed printings with hundreds of channels. Based on such approach, the authors experimentally encode, respectively, 25 gray scale printings into 25 angles and even 8 gray scale videos into 8 angles with a phase‐only spatial light modulator. As a bridge between printings and holograms, this method allows to generate printings combining various holographic methods. Beneficial from this, a gradient metasurface based 324 channel printing is demonstrated which multiplexes angles, polarizations, and wavelengths simultaneously. This work paves the way to flexibly angle‐dependent printing display and massively multiplexed encryption systems. Abstract : In this work, a novel angle multiplexed printing design method combining holographic approaches is proposed for boosting the amounts of channels in single printing element. A static 25 channel printing and a dynamic 8 channel video display are experimentally demonstrated using a spatial light modulator. Another 324 channel printing based on a gradient metasurface is illustrated through simulation.